Comparative Study of the Sedative and Anti-nociceptive Effects of Sacrococcygeal Epidural Administration of Romifidine, Lidocaine, and Romifidine/Lidocaine in the Dromedary Camel - Marzok, Mohamed; Almubarak, Adel I.; Abdel-Raheem, Sherief M.; El-khodery, Sabry; Shawaf, Turke; Kandeel, Mahmoud (Frontiers in Veterinary Science, 2022)
This study evaluates the clinical usefulness and compares the sedative and anti-nociceptive effects of romifidine (RO), a combination of romifidine-lidocaine (ROLD), and lidocaine (LD) alone administered in the camel’s epidural space. In a randomized prospective study, eighteen healthy adult dromedary camels were assigned randomly to three treatment groups (n=6), each receiving 50 μg/kg of RO, 0.30 mg/kg of LD, or a combination of both RO and LD epidurally. All treatments were expanded in 0.9% sterile normal saline solution to 0.05 mL/kg. The total dose volume of 20 ml was administered directly into the sacrococcygeal space. After epidural injection of each treatment, the onset time, duration, anatomical extension of anti-nociception, and sedation were documented. Anti-nociception was tested at different areas using a pinprick test and artery forceps pinching at the perineum and inguinal area. RO and ROLD treatments resulted in mild to severe sedation and complete bilateral analgesia with loss of sensation in the tail, perineum, scrotum in males, vulva in females, the caudal aspect skin of the upper hind limb, and inguinal region (udder in females and the prepuce in males). The anatomic extent of anti-nociception reached the chest cranially and the footpad distally. Our results indicate the possibility of utilizing RO and ROLD combinations in clinical practice to produce a very effective and safe method of enabling many surgical and obstetrical procedures to be completed either in the standing or recumbent position and providing a long period of postoperative pain relief.